Analysis of Social Interaction of Inclusion Students at SMP Muhammadiyah - Nufitriani Kartika Dewi; Syifa Fauziyah (Ananda: Jurnal Pendidikan Anak dan Remaja, 2025)
This study discusses the importance of social interaction in the context of inclusive education, especially for students with special needs at SMP Muhammadiyah. Social interaction not only plays a role in academic development, but also in the formation of students' character and social abilities. This study uses a descriptive qualitative approach with literature study techniques, observations, interviews, and documentation to examine the role of teachers and factors that affect the social interaction of inclusion students. The results of the study show that teachers have a central role in accompanying and facilitating students with special needs through adaptive learning strategies. In addition, support from peers and the school's social environment also contribute to the success of students' social interactions. Although there are still obstacles in the implementation of inclusive education, collaboration between teachers, students, and the school environment is considered to be able to create a learning environment that supports the optimal development of inclusive students.